Anomalous echo: Exploring abnormal experience correlates of emotional motor resonance in Schizophrenia Spectrum. Issue 1 (30th September 2015) - Sestito, Mariateresa; Raballo, Andrea; Umiltà, Maria Alessandra; Amore, Mario; Maggini, Carlo; Gallese, Vittorio
Abstract: Anomalous experiences such as Basic Symptoms (BS) are considered the first subjective manifestation of the neurobiological substrate of schizophrenia. The purpose of this study was to explore whether a low or high emotional motor resonance occurring in Schizophrenia Spectrum (SzSp) patients was related to patients׳ clinical features and to their anomalous subjective experiences as indexed by the Bonn Scale for the Assessment of Basic Symptoms (BSABS). To this aim, we employed a validated paradigm sensitive in evoking a congruent facial mimicry (measured by means of facial electromyographic activity, EMG) through multimodal positive and negative emotional stimuli presentation. Results showed that SzSp patients more resonating with negative emotional stimuli (i.e. Externalizers ) had significantly higher scores in BSABS Cluster 3 ( Vulnerability ) and more psychotic episodes than Internalizers patients. On the other hand, SzSp patients more resonating with positive emotional stimuli (i.e. Externalizers ) scored higher in BSABS Cluster 5 ( Interpersonal irritation ) than Internalizers . Drawing upon a phenomenological-based perspective, we attempted to shed new light on the abnormal experiences characterizing schizophrenia, explaining them in terms of a disruption of the normal self-perception conveyed by the basic, low-level emotional motor mechanisms. Highlights: We combined phenomenology and neurophysiology by adopting a trans-domain approach. We investigated the experiential correlates of motor facial mimicry in Schizophrenia Spectrum. Participants were divided based on the intensity of their emotional motor resonance. Externalizers – Internalizers differed for subjective experiences and clinical traits. Abnormal experiences seem related to low-level emotional motor mechanisms disruption.